Hubungan Bobot Potong dan Bobot Karkas dengan Yield Grade dan Rib Eye Muscle Area pada Kambing Jawarandu Jantan - Rizki, Muhammad; Muthalib, R.A; Farizal, Farizal; Afzalani, Afzalani; Raguati, Raguati; Sulaksana, Indra; Pradana, Erbid Dwi (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study was conducted to evaluate the relationship between slaughter weight and carcass weight with yield grade and Rib Eye Muscle Area (udamaru) in male Jawarandu goats. The research involved 30 male Jawarandu goats slaughtered at the Mat Beken Slaughterhouse, Jambi City, which were classified into two age groups, namely I2 (2–2.5 years) and I3 (3–3.5 years). Data collected included slaughter weight, carcass weight, yield grade, and Rib Eye Muscle Area, and were analyzed using simple and multiple linear regression methods.The results indicated that in the individual age groups I2 and I3, the relationship between slaughter weight and carcass weight with yield grade and Rib Eye Muscle Area was not statistically significant. However, in the combined age group analysis using multiple linear regression, slaughter weight and carcass weight showed a highly significant effect (P